2018
DOI: 10.3390/pharmacy6040103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of General Public’s Knowledge and Opinions towards Antibiotic Use and Bacterial Resistance: A Cross-Sectional Study in an Urban Setting, Rufisque, Senegal

Abstract: Background: Bacterial resistance is a major public health problem worldwide. One solution to this scourge is to sensitize the general public on rational use of antibiotics. Our goal was to assess people’s knowledge and opinions about antibiotic use and bacterial resistance in an urban setting. Method: We performed a cross-sectional study. A convenience sampling was done. A questionnaire was administered to 400 persons during face-to-face interviews. Results: Most respondents thought that antibiotics are effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
2
8
0
2
Order By: Relevance
“…Only 17.8% of Thai respondents had received information about antibiotic use and AMR in the past twelve months, almost half that of those in the European study, where 33% had received information [3]. Similarly, this study shows that low levels of education are negatively associated with receiving information which confirmed a study from Poland [30]. Promoting public knowledge on antibiotics and AMR needs to also focus on disadvantaged groups such as poor and uneducated people.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Only 17.8% of Thai respondents had received information about antibiotic use and AMR in the past twelve months, almost half that of those in the European study, where 33% had received information [3]. Similarly, this study shows that low levels of education are negatively associated with receiving information which confirmed a study from Poland [30]. Promoting public knowledge on antibiotics and AMR needs to also focus on disadvantaged groups such as poor and uneducated people.…”
Section: Discussionsupporting
confidence: 75%
“…Sources of information vary across countries due to different contexts and policy interventions. For example, a study in Senegal showed that family or friends are the most common source (58.5%), followed by pharmacy staff (54.5%) and doctors or nurses (25%) whereas the Eurobarometer 445 showed that the most common sources were doctors (32%), television advertisements (27%) and television news (26%) [3, 30]. As health professionals were the main source of information about antibiotics and AMR, policy interventions should mobilize physicians, nurses and pharmacists as effective change agents to deliver correct messages during all clinical encounters on the use of antibiotics in order to strengthen AMR awareness in the population.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that respondents with at least one family member working as a healthcare professional possessed better antibiotic knowledge and perception at baseline. Public preference to seek informal advice from family and friends rather than formal healthcare was observed in previous studies [37,38]. These observations were in-line with previous recommendations and highlighted social network support as one of the measures in promoting public health [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…Katılımcıların %75.4'ü bakteriyel dirençle mücadelede büyük bir rol oynadıklarına inanıyordu. DSÖ araştırmasına göre katılımcıların %57'sinin bakteriyel direnci durdurmak için fazla bir şey yapamadıkları rapor edilmiştir (13) . Bizim sonuçlarımız da öğrencilerin bakteriyel dirence karşı başlatabilecekleri eylemlerin yeterince farkında olmadığını göstermektedir.…”
Section: Discussionunclassified
“…Veri toplama aracı: Çalışmanın potansiyel öğelerini belirlemek için önceki benzer çalışmaların literatür taraması yapılmıştır. Literatür taramasına dayanarak, çalışma anketi daha önce Birleşik Krallık, Senegal ve İsveç'te kullanılan doğrulanmış anketlerden uyarlanmıştır (12)(13)(14) . Çalışma verileri anket formları ile nicel olarak toplanmış ve analizler nicel veriler üzerinden gerçekleştirilmiştir.…”
Section: Gereç Ve Yöntemunclassified